Effects of inhaled fluticasone on angiogenesis and vascular endothelial growth factor in asthma. Issue 4 (14th November 2006) - Feltis, B N; Wignarajah, D; Reid, D W; Ward, C; Harding, R; Walters, E H
Abstract : Background: Subepithelial hypervascularity and angiogenesis in the airways are part of structural remodelling of the airway wall in asthma, but the effects of inhaled corticosteroids (ICS) on these have not been explored. Increased vascularity in asthma may contribute to a number of functional abnormalities. A study was undertaken to explore angiogenic modulation by ICS and its likely regulation via vascular endothelial growth factor (VEGF), its receptors and the angiopoietins. Methods: A placebo-controlled intervention study with ICS in asthma was performed, examining vascularity, VEGF, its receptors (VEGFR1 and VEGFR2), and angiopoietin-1 (Ang1) to assess which of these factors were changed in the asthmatic airways after ICS treatment. Airway wall biopsy specimens, lavage fluid and cells were obtained from 35 patients with mild asthma randomised to receive ICS or placebo for 3 months, after which bronchoscopic examination and sample collection were repeated. Immunohistochemistry and image analysis were used to obtain quantitative measures of vessels, angiogenic sprouts, VEGF, VEGFR1, VEGFR2 and Ang1 staining in airway biopsy specimens. ELISA was used to assess VEGF concentrations in the lavage fluid. Results: Vessel, VEGF and sprout staining were decreased after 3 months of ICS treatment. VEGF levels remained unchanged. VEGF receptors and Ang1 staining were not reduced after treatment. Conclusions: The findings of this study support an effect of ICS in downregulating angiogenic remodelling in the airways in asthma, associated with decreasing VEGF activity within the airway wall. The environment of the airways after treatment with ICS, with changes in the balance between VEGF, its receptors, Ang1 and sprouts, appears to be less angiogenic than in untreated asthma.